853Could baseline electrical parameters be a marker of arrhythmia occurrence and poorer prognosis in implantable cardioverter defibrillator patients?. (18th June 2020) - Zecchin, M; Solimene, F; D"onofrio, A; Zanotto, G; Iacopino, S; Pignalberi, C; Calvi, V; Maglia, G; Della Bella, P; Quartieri, F; Curnis, A; Biffi, M; et al.
Abstract: Funding Acknowledgements: This research did not receive any specific grant from funding agencies in the public, commercial, or not-for-profit sectors. Background/Introduction: Parameters routinely measured during cardiac devices implantation also depend on bioelectrical properties of the myocardial tissue. Purpose: To explore the potential association of electrical parameters with clinical outcomes in implantable cardioverter-defibrillator (ICD) and cardiac resynchronization therapy defibrillators (CRT-D) recipients. Methods: In the framework of the Home Monitoring Expert Alliance, baseline electrical parameters for all implanted leads were compared by occurrence of all-cause mortality, adjudicated ventricular arrhythmia (VA) and atrial high rate episode lasting ≥7 days (7day-AHRE). Results: In a cohort of 2, 976 patients (58.1% ICD) with a median follow-up of 25 months, events rates were 3.1/100 patient-years for all-cause mortality, 18.1/100 patient-years for VA and 8.9/100 patient-years for 7day-AHRE. At univariate analysis baseline shock impedance was consistently lower in groups with events than in those without, with a 40 Ohm cut-off better identifying patients at high risk, but at multivariable analysis the adjusted-hazard ratios (HRs) lost statistical significance for any endpoint. Baseline atrial sensing amplitude during sinus rhythm was lower in patients with 7-day AHRE as compared to those without (2.40 [IQ: 1.62-3.71] Vs 3.50 [IQ: 2.35-4.66] mV, p < 0.01). The adjusted-HR for 7-day AHRE in patients with atrial sensing >1.5 mV versus those with values ≤1.5 mV was 0.44 (95% CI:0.27-0.72), p = 0.001. Conclusion: Despite in patients with events a lower baseline shock impedance was observed at univariate analysis, the association lost statistical significance at multivariable analysis. Conversely, low sinus rhythm atrial sensing (≤1.5 mV) measured with standard transvenous leads could identify subjects at high risk of long-lasting atrial arrhythmia.